Dinutuximab Synergistically Enhances the Cytotoxicity of Natural Killer Cells to Retinoblastoma Through the Perforin-Granzyme B Pathway - Wang, Huixue (Onco Targets Ther, 2020)
PURPOSE: Conventional chemotherapy and enucleation usually fail to cure advanced retinoblastoma. We investigated the retinoblastoma immune microenvironment and the efficacy of the combination of dinutuximab and CD16-expressing NK-92MI (NK-92MI(hCD16-GFP)) cells on retinoblastoma cells in this study. PATIENTS AND METHODS: Immunohistochemistry and flow cytometry (FC) were performed to assess the expression level of GD2 in retinoblastoma tissues and cells. Gene set enrichment analysis (GSEA), immunohistochemisrztry and immunocytochemistry were conducted to assess the retinoblastoma immune microenvironment and the integrity of the blood-retinal barrier (BRB). After overexpressing CD16 in NK-92MI cells, fluorescence-activated cell sorting (FACS) was applied to select the positive subpopulation. LDH assays and FC were used to detect LDH release and apoptosis in retinoblastoma cells subjected to a combination of dinutuximab and NK-92MI(hCD16-GFP) cells. Finally, the release of perforin-granzyme B and the expression of CD107a in NK-92MI(hCD16-GFP) stimulated by retinoblastoma cells were assessed via enzyme-linked immunosorbent assays (ELISAs) and FC in the presence of dinutuximab or an isotype control. RESULTS: GD2 was heterogeneously expressed in retinoblastoma tissues and cell lines and positively correlated with proliferation and staging. GSEA revealed the immunosuppressive status of retinoblastoma microenvironment. The immune cell profile of retinoblastoma tissues and vitreous bodies suggested BRB destruction. LDH release and apoptosis in retinoblastoma cells caused by NK-92MI(hCD16-GFP) cells were significantly enhanced by dinutuximab. Finally, the release of perforin-granzyme B and the expression of CD107a in NK-92MI(hCD16-GFP) cells stimulated by retinoblastoma cells were obviously increased by dinutuximab. CONCLUSION: This study indicates that retinoblastoma impairs the integrity of the BRB and contributes to dysregulated immune cell infiltrates. GD2 is a specific target for natural killer (NK) cell-based immunotherapy and that the combination of dinutuximab and NK-92MI(hCD16-GFP) cells exerts potent antitumor effects through antibody-dependent cell-mediated cytotoxicity.